Potensi Pewarna Makanan Alami Pada Jajanan Pasar Sebagai Bahan Ajar Kimia Dasar Untuk Meningkatkan Literasi Mahasiswa - Fatchiyatun Ni’mah (Jurnal Pendidikan Indonesia (JOUPI), 2023)
Chemical literacy involves not only comprehending chemical laws and theories but also understanding their applications in everyday life. One of the ways to enhance chemical literacy is by utilizing materials commonly encountered as teaching aids. “Jajanan Pasar”, a culinary heritage of the archipelago, hold considerable potential due to their distinctive colors. A literature review of various articles revealed the presence of secondary metabolites—natural dyes or pigments—from various plants commonly utilized as food colorants for traditional snacks. These include chlorophyll, flavonoids, betalains, and carotenoids. The unique chemical properties of these secondary metabolites offer potential applications in diverse chemical labs, including extraction, acid-base indicators, and renewable energy.